2015
DOI: 10.3174/ajnr.a4340
|View full text |Cite
|
Sign up to set email alerts
|

Aqueductal Stroke Volume: Comparisons with Intracranial Pressure Scores in Idiopathic Normal Pressure Hydrocephalus

Abstract: BACKGROUND AND PURPOSE:Aqueductal stroke volume from phase-contrast MR imaging has been proposed for predicting shunt response in normal pressure hydrocephalus. However, this biomarker has remained controversial in use and has a lack of validation with invasive intracranial monitoring. We studied how aqueductal stroke volume compares with intracranial pressure scores in the presurgical work-up and clinical score, ventricular volume, and aqueduct area and assessed the patient's response to shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
4
45
1
1
Order By: Relevance
“…Ringstad et al. previously described a similar finding; that is, stroke volume was correlated to ventricular volume . Similarly, the reduced pulsatility of the cervical CSF, in agreement with some previous findings but in contradiction to others, may reflect an overall redistribution of the intracranial CSF volume, as it has been suggested that the supratentorial subarachnoid space may be reduced in INPH, as part of the so‐called DeSH sign .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ringstad et al. previously described a similar finding; that is, stroke volume was correlated to ventricular volume . Similarly, the reduced pulsatility of the cervical CSF, in agreement with some previous findings but in contradiction to others, may reflect an overall redistribution of the intracranial CSF volume, as it has been suggested that the supratentorial subarachnoid space may be reduced in INPH, as part of the so‐called DeSH sign .…”
Section: Discussionsupporting
confidence: 82%
“…This has been suggested, but not confirmed, as an efficient predictive test for outcome after surgery. It is also unclear whether the increase in pulsatility is caused by a reduced intracranial compliance or by an increased ventricular volume …”
Section: Introductionmentioning
confidence: 99%
“…All these extra imaging studies increase the total examination time, require experience and affect patient compliance negatively. Besides, their efficacy in diagnosis and prediction of response to the shunt operation are debatable [26][27][28][29].…”
Section: Normal Pressure Hydrocephalusmentioning
confidence: 99%
“…As demonstrated by Ringstad et al, 1 neurosurgeons seem to be comfortable with placing an ICP monitor in the brain to measure compliance. If you are a radiologist, PCMR to measure the ASV may be the preferred technique.…”
mentioning
confidence: 99%